The differences between medalists and non-medalists at the 2008 Olympic Games taekwondo tournament - Cular, D.; Krstulovic, S.; Tomljanovic, M. (Human Movement, 2011)
To establish the differences in some morphological characteristics and competitive efficacy parameters between the medal winners and other competitors in male and female competitions at the Olympic taekwondo tournament in China 2008. Basic procedures. Athlete profiles were obtained from the "Official Olympic site" which included weight category, weight, height, age, given points, received points, warnings, deduction points, defensive/offensive kicks, and punches. A total of 128 athletes competed (64 males and 64 females) in the Games. Main findings. In males ANOVA found significant differences in both the sub patterns between the medal winners and other competitors in: the average number of given points per fight, average number of points received per fight, and average number of given defensive kicks to the trunk. Among females, significant differences were found in all the previously specified variables together with the average number of given offensive points to the trunk, average number of given offensive points to the head, and average number of warnings per fight. Conclusions. The differences between male medalists and non-medalists were observed in the DK1P (average number of defensive kicks to the trunk) variable, whereas in the female competitors the largest differences were in the average number of offensive points to the trunk and head (OK1P and OK2P). The medal winners achieved better results in those variables when compared with non-winners in both male and female categories. In comparison to the last two Olympic games, certain changes in the trend in how points are given among the male and female competitors are evidenced. When compared with the 2000 and 2004 Olympic games, the Beijing games were dominated by defensive kicks among the male competitors, whereas in female athletes, greater homogeneity and changes in the style of fighting were observed.